Analisis Protokol Routing Reactive pada Jaringan Vehicular Ad Hoc Network (VANET) dengan Model Skenario Jalan Tol - Muhammad Syauqi Dhiaulhaq (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
VANET is an ad hoc network that spreads through moving objects, connecting them in network range and enabling communication or interaction among them. VANET has High Mobility and Dynamic Network Topology characteristics. The network topology will change quickly as a result of each moving node. As a result, routing protocols are required for all network operations, including message transmission and route searching, which is handled by each node. This research implements and tests the DSR and AODV routing protocols in a VANET environment in the NS-2 network simulator, where performance studies are carried out on the DSR and AODV protocols by simulating toll road scenarios and different numbers of nodes. In testing this, there are several metrics used including throughput, packet delivery ratio and end to end delay (E2D). The performance of VANET using the DSR routing protocol is better compared to the AODV routing protocol, with the DSR obtained an average value for the end-to-end delay metric of 10379.83ms compared to AODV with an average value of 10651.63ms. Then, with the DSR routing protocol, an average value of 84.51% was obtained for the packet delivery ratio metric compared to AODV which obtained an average value of 82.94%. Then, with the DSR routing protocol, an average value of 295.10 Kbps was obtained for the throughput metric compared to AODV which obtained an average value of 289.18 Kbps.